Mapping knowledge landscapes and emerging trends of the links between osteoarthritis and osteoporosis: A bibliometric analysis - Wan, Xin; Wang, Xuefei; Pang, Ran; Xu, Chunlei; Shi, Wei; Zhang, Huafeng; Li, Hui; Li, Zhijun (Frontiers in Public Health, 2022)
Background: Osteoarthritis is a common chronic irreversible joint disease characterized by degenerative changes of articular cartilage and secondary hyperosteogeny. The progression of the disease affects not only the articular cartilage, but also including the subchondral bone, joint capsule, and synovial membrane. Multiple studies have revealed that patients with osteoarthritis were found to have a significantly increased risk of osteoporosis, which also contributes to the progression of osteoarthritis. Nevertheless, no attempt has been made to analyze the field of osteoarthritis and osteoporosis research with the bibliometric. This study aims to comprehensively review the cooperation and influence of countries, institutions, authors, and journals in the field of osteoarthritis and osteoporosis from the perspective of bibliometrics, evaluate the clustering evolution of knowledge structure, and discover hot trends and emerging topics. Methods: Search the Web of Science core collection in Science Citation Index Expanded for articles and reviews of research on osteoarthritis and osteoporosis from 1998 to 2021. Bibliometric tools such as VOSviewer, and CiteSpace, were used in this study. The main analyses include cooperative relationships between countries, institutions, authors, co-citation analysis of authors, journals, co-occurrence analysis of keywords, and subject categories, as well as analyze of keywords. Results: A total of 1078 publications were included over the period 1998-2021. The number of annual publications on the relationship between osteoarthritis and osteoporosis is on the rise worldwide. The United States has made the greatest contribution and the Boston University was the most prolific institution. Reginster JY published the most papers among the publications, while Felson DT had the most co-citations. Respectively. Osteoarthritis And Cartilage was the most productive journal in this area of research. The keywords “inflammation”, “expression”, and “mesenchymal stem cells” also may be the focus of new trends and future research. Conclusions: In this study, bibliometrics and visual methods were used to conduct a comprehensive visual analysis of the current status of related research on the relationship between osteoarthritis and osteoporosis. Our results can provide scholars with key information in this field, better understand the dynamic changes of research hotspots in this field, and provide guidance for determining potential research directions.